Investigation of Carbon Footprints of Three Desalination Technologies: Reverse Osmosis (RO), Multi-Stage Flash Distillation (MSF) and Multi-Effect Distillation (MED) - Do Thi, Huyen Trang; Tóth, András József (Periodica polytechnica. Chemical engineering., 2023)
Nowadays, the drinking water shortage is increasing, mainly due to rapid population growth, climate change, wasteful overuse of water, and pollution. Under the current circumstances, a quarter of the world's population will not have access to good quality drinking water. Thus, another solution must be adopted in areas with insufficient freshwater. One possible line is the desalination of seawater, one of the most practical solutions to solve the problem of drinking water shortage along the oil availability shore and continues to expand globally. Water produced may also be utilized for irrigation, reducing a region's reliance on imports, contributing to the local economy, and improving food supplies. However, this process is not a consequences-free procedure; it may cause several environmental and human health problems.The three most applied desalination technologies are reverse osmosis (RO), multi-stage flash distillation (MSF), and multi-effect distillation (MED). In this study, the emissions of greenhouse gases (GHGs) of drinking water produced from seawater using these three technologies with fossil and renewable energy sources were investigated based on two methods: life cycle assessment (LCA) using SimaPro life cycle analysis software and carbon footprints. As a result, RO technology has significantly lower CO2 emissions than thermal technologies. The RO combined renewable energy is the most environmentally friendly; provides outstanding benefits in terms of human health and ecosystem quality. This technology may still evolve in the future to produce longer-lasting, cheaper membranes, and the energy requirements of this process are lower with applying modern energy recovery systems.